Gerenciamento de impressão das narrativas contábeis, regulação econômica e previsões de analistas: evidências sobre o Brasil - Castro, Lívia Arruda (2023)
Economic regulation seeks to promote a safe and reliable institutional environment for economic agents, providing an incentive for companies to improve their disclosure practices. Considering these aspects, we question whether economic regulation is capable of reducing Analyst forecast errors, once they use, among other tools, the financial reports disclosed by the companies. Previous studies indicate that the analysts use even accounting narratives of the financial reports to formulate their forecasts. On the other hand, accounting narratives can be manipulated by managers through opportunistic Impression Management practices, with the intention of controlling the perception of their stakeholders and deceiving them regarding their economic performance. Therefore, there is an expectation that economic regulation will affect the information environment of companies, leading, for example, to a reduction in printing management practices for accounting narratives, which may, in turn, be associated with a reduction in errors in analyst forecasts. Thus, based on the assumptions of Agency Theory, this thesis investigated the effect between the economic regulation and analyst forecasts of Brazilian companies, and if the relation is mediated by the impression management of accounting narratives. To this end, its fundamental argument is that economic regulation acts as a form of monitoring managers, reducing moral hazard problems, and, therefore, inhibiting impression management practices of accounting narratives. Given higher quality accounting information, analysts would be able to reduce the estimated error of their earnings forecasts. The sample consisted of 5,299 quarterly observations of 256 companies listed on B3, in the period 2003-2021, based on data collected from Thomson Reuters® and Comdinheiro®. The impression management of the sample companies was obtained from the analysis of the earnings release report of the sample companies, using the Watson NLU software, developed by IBM®. The estimations were conducted using a Structural Equation Model, since this method allows for the simultaneous examination of several variables. The findings suggest that economic regulation reduces companies' level of impression management, indirectly minimizing analysts' forecast errors. Thus, it can be stated that the impression management of accounting narratives is a mediating variable in the relationship between economic regulation and analysts' forecast errors, at a level of 5%, confirming the thesis of this research. On the other hand, the empirical evidence obtained also showed that economic regulation, in itself, appears to be incapable of reducing errors in analysts' forecasts, possibly because it modifies several other factors at the level of the company, the environment and market dynamics. , which together can be positively or negatively associated with analysts' forecasts, so that together they weaken the effect of the informational benefits of economic regulation on analysts' forecast errors